A novel ensemble method for retrieving properties of warm cloud in 3‐D using ground‐based scanning radar and zenith radiances. Issue 18 (23rd September 2014) - Fielding, Mark D.; Chiu, J. Christine; Hogan, Robin J.; Feingold, Graham
Abstract We present a novel method for retrieving high‐resolution, three‐dimensional (3‐D) nonprecipitating cloud fields in both overcast and broken‐cloud situations. The method uses scanning cloud radar and multiwavelength zenith radiances to obtain gridded 3‐D liquid water content (LWC) and effective radius (re) and 2‐D column mean droplet number concentration (Nd). By using an adaption of the ensemble Kalman filter, radiances are used to constrain the optical properties of the clouds using a forward model that employs full 3‐D radiative transfer while also providing full error statistics given the uncertainty in the observations. To evaluate the new method, we first perform retrievals using synthetic measurements from a challenging cumulus cloud field produced by a large‐eddy simulation snapshot. Uncertainty due to measurement error in overhead clouds is estimated at 20% in LWC and 6% in re, but the true error can be greater due to uncertainties in the assumed droplet size distribution and radiative transfer. Over the entire domain, LWC and re are retrieved with average error 0.05–0.08 g m−3 and 2 µm, respectively, depending on the number of radiance channels used. The method is then evaluated using real data from the Atmospheric Radiation Measurement program Mobile Facility at the Azores. Two case studies are considered, one stratocumulus and one cumulus. Where available, the liquid water path retrieved directly above the observation site was found to be in good agreement with independent values obtained from microwave radiometer measurements, with an error of 20 g m−2.